Efeito agudo do exercício submáximo na função pulmonar, endotelial e na resposta autonômica cardíaca de mulheres asmáticas - Pierazzo, Gabriele Da Dalto (Universidade Federal de São Carlos, 2025)
Asthma is a chronic non-communicable disease characterized by chronic inflammation of the airways and variable limitation of expiratory airflow. In addition to respiratory symptoms, asthmatic individuals often present systemic repercussions of the disease, such as changes in cardiac autonomic control and endothelial dysfunction. Exercise is part of the pulmonary rehabilitation of this population, but the interaction of acute submaximal exercise with the cardiopulmonary function of asthmatic women is still unknown. Objective: To evaluate the effect of submaximal exercise on endothelial function, cardiac autonomic control, and pulmonary function in women with asthma. Methods: This is a cross-sectional study involving 34 women, distributed in two groups: 17 in the control group (CG) and 17 in the asthma group (AG). The evaluations were performed in two visits, with the tests and evaluations of pulmonary function, endothelial function, and cardiac autonomic modulation in one visit. Endothelial function was assessed by flow-mediated dilation of the brachial artery and was collected at two time points: 1) Baseline; 2) Immediately after submaximal exercise. Heart rate variability was collected at three time points: 1) Rest; 2) During submaximal exercise; 3) Recovery from submaximal exercise. Pulmonary function was assessed at two time points: 1) Baseline; 2) After submaximal exercise; Results: The participants had a mean overall age of 30.32±7.26 years, with a mean height of 162.97±4.55 cm, weight of 68.07±15.64 kg and BMI of 25.49±5.23. Submaximal exercise resulted in a decrease in Forced Vital Capacity (FVC) (L) in AG, while it did not generate significant effects in CG. After exercise, an increase in basal shear was observed in CG (P 0.05). Regarding cardiac autonomic control, a sympathetic predominance was observed at rest in AG and parasympathetic in CG, and higher Mean HR values during exercise in CG when compared to AG (p<0.05). Conclusion: Submaximal exercise was able to reduce FVC (L) in AG. There was a sympathetic predominance at rest in AG and parasympathetic in CG. Regarding vascular function, although AG presented higher basal values of basal shear, post-hyperemia flow and post-hyperemia shear, only in CG did basal shear increase after exercise.
Acute effect of submaximal exercise on pulmonary and endothelial function and cardiac autonomic response in asthmatic women
Keywords: Asma; Exercício; Função pulmonar; Função endotelial; Resposta autonômica cardíaca; Asthma; Exercise; Pulmonary function; Vascular function; Cardiac autonomic; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL